2013
DOI: 10.15835/nsb539088
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation for Grain Yield and Related Traits in Temperate Red Rice (Oryza sativa L.) Ecotypes

Abstract: The present study was carried out in Kashmir (India) to assess the genetic variability for grain yield and component traits among 14 red rice ecotypes from temperate region (locally known as Zag for its coloured kernels) and correlation and path coefficients were also studied for fifteen agro-morphological characters. Genotypic and phenotypic coefficients of variation were high for grain yield, secondary branches per panicle and panicle weight; moderate for grain number per panicle, grain length:breadth (L:B) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 9 publications
(6 reference statements)
0
13
0
1
Order By: Relevance
“…In general, traditional rice cultivar contained several important genes related to acidity tolerance, salinity, and metals contamination (Ogunbayo et al 2007). Further, this germplasm is shaped for a long time by the interplay between farmer selection and adapted to the local conditions (Sanghera et al 2013). Hence, its becomes an indispensable part of the local culture and traditions of ricegrowing people across Asia over many generations (Thomson et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In general, traditional rice cultivar contained several important genes related to acidity tolerance, salinity, and metals contamination (Ogunbayo et al 2007). Further, this germplasm is shaped for a long time by the interplay between farmer selection and adapted to the local conditions (Sanghera et al 2013). Hence, its becomes an indispensable part of the local culture and traditions of ricegrowing people across Asia over many generations (Thomson et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Out of 50 morphological, physiological and disease resistant traits, 33 traits including LL were significantly correlated with DF in temperate japonica rice (Hori et al, 2012). A significant correlation was observed for DF with PL and PW (Ashfaq et al, 2012) while CN and grain yield was found to be positively correlated for 14 red rice genotypes of Indian rice by Sanghera et al (2013). CD correlates with PL and SW correlates with PW for the PCA of flowered accessions in this study.…”
Section: Correlation Analysis Among Days To Flowering and Morphologicmentioning
confidence: 47%
“…Accessions of similar morphology were grouped in to individual clusters in Hierarchical cluster analysis (Supplementary table 1 accessions, 6 (5612, 5611, 5610, 3257, 3489, 6282) 2014). Genetic basis for variations in pericarp color and lemma and palea color had been previously described by Chandrarathna (1964) and Sanghera et al (2013). Among the seed characters of not-flowered accessions in core collection, Ma wee 4561 was an awn-less variety with white pericarp color which was different from other representative accessions of not-flowered dendrogram with awns and brown or light brown pericarp color.…”
Section: Varietal Diversity Of the Total Collection Of Traditional Rimentioning
confidence: 89%
“…The treatments were arranged in a split-plot design such as 5 -G R200 -1-2 and radix accession. The main plot was the soil moisture of 25, 50, 75 and 100% (control).…”
Section: Methodsmentioning
confidence: 99%
“…4 Red rice paddy accession has longer time to harvest (121-138 days) with a flowering time of 91-107 days. 5,6 Red rice accession is not classified as drought tolerant so it has lower yield (an average of 2 tons/ha). 7 Currently, there is only one variety of red rice classified as upland types, which is Inpago 7 (4.6 tons/ha).…”
Section: Introductionmentioning
confidence: 99%